The effect of nano-hydroxy apatite on re-mineralize white spot lesions prior to orthodontic adhesive removal by different techniques (An In vitro comparative study) - Malik, Saja Sami S; Ghaib, Nidhal H (Journal of Baghdad College of Dentistry, 2017)
Background: White-spot lesion is one of the problems associated with the fixed orthodontic treatment. The aims of this in-vitro study were to investigate enamel damage depth on adhesive removal when the adhesive were surrounded by sound, demineralized or demineralized enamel that had been re-mineralized prior to adhesive removal using 10% Nano-Hydroxy apatite and to determine the effect of three different adhesive removal techniques.Materials and methods: Composite resin adhesive (3M Unitek) was bonded to 60 human upper premolars teeth which were randomly divided in to three groups each containing ten sound teeth and ten teeth with demineralized and re-mineralized lesions adjacent to the adhesive. A window of 2 mm was prepared on the buccal surface of the tooth and painted with an acid resistant nail varnish except for the window.The demineralized enamel produced by immersion of teeth in demineralization buffer for 12 days.half of the demineralized window, was covered with acid –resistant red nail varnish, and the samples were then subjected to re-mineralization with 10% of nano hydroxyapatite. The adhesive was removed with either :(1) fiber reinforced composite bur in slow speed handpiece (SS); (2)12 fluted long flame carbide bur in high speed handpiece (HS); (3) ultrasonic scaler (US).damage to the enamel was assessed using stereomicroscope with grid eye piece.Results: the greatest to least mean depth of damage with three different adhesive removal techniques to sound enamel was HS˃ US ˃SS and to demineralized and re-mineralized enamel were SS ˃US˃ HS. Sound enamel had the least amount of damage. Re mineralization before the adhesive removal highly significant reduced the amount of damage produced by all techniques compared with demineralized enamel.Conclusions: When the demineralized enamel was present 12 fluted long flame carbide bur were found to be the least damage in adhesive removal technique and re-mineralization further reduced the amount of enamel damage